The Absent Traveller is Still Far From the River - Mukherjee, Sujit (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1997)
AbstractThrough the examination of two recent and one older translation of an ancient Indian anthology of poems the various strategies of appropriation of the text are brought to the fore. Questions are raised concerning the transformation brought about through translation, the forms the recovery of an ancient text can take.